THU0680 ANTI-PEPTIDYL-ARGININE DEIMINASE 3 AND 4 AUTOANTIBODIES IN A COHORT OF RHEUMATOID ARTHRITIS WITH INTERSTITIAL LUNG DISEASE. (June 2019) - Palterer, Boaz; Vitiello, Gianfranco; D'onofrio, Bernardo; Vivarelli, Emanuele; Cammelli, Daniele; Giudizi, Maria Grazia; Martinez-Prat, Laura; Casas, Silvia; Bentow, Chelsea; Mahler, Michael; Parronchi, Paola
Abstract : Background: Interstitial lung disease (ILD) affects up to 30% of patients with rheumatoid arthritis (RA). Peptidyl-arginine deiminases (PAD) are key enzymes in RA pathogenesis as they are involved in the citrullination of proteins, targets of anti-citrullinated protein antibodies (ACPA). Although RA-ILD significantly contributes to disease burden including mortality, diagnostic and prognostic biomarkers are still lacking. Objectives: To measure anti-PAD3 and anti-PAD4 antibodies in a cohort of RA and compare their prevalence in patients with and without ILD. To assess the associations of anti-PAD3, anti-PAD4 and ACPA with disease activity, joint erosions, lung involvement and smoking history. Methods: A total of 71 patients fulfilling the 2010 ACR/EULAR RA Classification Criteria were recruited; the mean age was 63.3±12.4 and 87% of them were females, 11 (15.5%) of them had been diagnosed with ILD. Demographic, clinical as well as radiological data were retrospectively collected. ILD was defined as usual interstitial pneumonia (UIP), non-specific interstitial pneumonia (NSIP) or indeterminate patterns on chest high-resolution computed tomography, according to ATS/ERS guidelines. Particle-based Multi-Analyte Technology (PMAT) (Inova Diagnostics, USA, research use only) was used to measure anti-PAD3 and anti-PAD4 autoantibodies. ACPA IgG were measured by chemiluminescence (QUANTA Flash CCP3, Inova Diagnostics, USA). Results: Anti-PAD4 levels were correlated with erosive disease (p=0.043) and morning stiffness (p=0.031). Anti-PAD3 and anti-PAD4 levels were associated to DAS28-ESR at the time of sampling (anti-PAD3, r=0.34, p=0.004; anti-PAD4, r=0.34, p=0.004). Anti-PAD4 antibodies were significantly lower in patients with ILD (p=0.043). There was no association between anti-PAD4 and smoking, while anti-PAD3 antibodies were higher in non-smokers (p=0.004). A strong correlation was found between anti-PAD4 and anti-PAD3 levels (r=0.73, p<0.0001). Conclusion: In our cohort, anti-PAD4 antibodies were correlated with joint erosions and RA disease activity, whereas a negative association with ILD was found. Smoking history was not associated with the presence and levels of anti-PAD antibodies. Our data validate the usefulness of anti-PAD4 antibodies as a biomarker for erosive disease. Further studies that take into account relevant confounders like therapy and larger RA-ILD cohorts are needed. References: [1] Darrah E, Martinez-Prat L, Mahler M (2019) Clinical Utility of Antipeptidyl Arginine Deiminase Type 4 Antibodies. J Rheumatol jrheum.180905 Disclosure of Interests: Boaz Palterer: None declared, Gianfranco Vitiello: None declared, Bernardo D'Onofrio: None declared, Emanuele Vivarelli: None declared, Daniele Cammelli: None declared, Maria Grazia Giudizi: None declared, Laura Martinez-Prat Employee of: Inova Diagnostics (Not pharmaceutical, diagnostics company), Silvia Casas Employee of: Inova Diagnostics, Chelsea Bentow Employee of: INOVA Diagnostics, Michael Mahler Employee of: Inova Diagnostics (Not pharmaceutical, diagnostics company), Paola Parronchi: None declared